STUDENTS’ PERCEPTION OF USING WHATSAPP IN EFL CLASSROOM - Raihan Fatkur Rahman syah; Daviq Rizal (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
The aim of this study was to describe studentsâ€™ percepon of using whatsapp in EFL classroom. This study applies a qualitative descriptive method. The subjects of this study were 18 students from the English Education Department of UIN Walisongo Semarang in the fifth semester of the academic year 2020. The researcher will use questionnaires in this study to determine students' perceptions of using Whatsapp in EFL Classroom. Based on the study's findings, it can be said that while WhatsApp is very user-friendly and a great learning tool, it cannot yet take the role of traditional classroom instruction. Students may communicate and interact with teachers and other students through WhatsApp. It also makes it easier to disseminate information and educational materials. Giving assignments through WhatsApp is also highly practical, and the collection is very beneficial for students. However, WhatsApp still has flaws. For example, fiber requires a significant internet allowance, which is obviously expensive, and a solid network is required. However, not all places in Indonesia have stable networks. The findings could be useful information for English language teachers who want to use Whatsapp application in their courses.Keywords: EFL Classroom, Mobile Application, Online Learning, Student Perception, Whatsapp Application.Â